EFEKTIVITAS PEMBERIAN SNACK BAR TAPE KETAN HITAM TERHADAP FREKUENSI DEFEKASI PADA REMAJA PUTRI - Seni Rahayu; Sri Wisnu Wardani; Gurid PE Mulyo (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
It is important to pay attention to the health of the reproductive tract of adolescents because it also determines the reproductive health of adolescents in the future. Teenagers tend to consume foods high in energy but low in fibre. That will trigger various problems and diseases related to the digestive organs, one of which is constipation. Fermented Black Glutinous Rice contains higher fibre content and better antioxidant activity because it has been fermented. Fermented Black Glutinous Rice has a high anthocyanin content that functions for health, such as preventing colon cancer. This study aims to determine the effectiveness of giving Fermented Black Glutinous Rice snack bars to the frequency of defecation in adolescent girls. This study used a pure experimental research design. The intervention group was given a Snack Bar much as one piece weighing 30 grams, while the control group was given education. The number of samples in this study was 38 people. Bivariable analysis was performed using the Independent T-Test and Wilcoxon Test Statistically. There was no significant difference in the frequency of defecation after giving the black sticky rice bar tape snack between the intervention and control groups with a p-value = 0.732 (p>0.05). This research needs to be carried out more deeply so that the effectiveness of giving Fermented Black Glutinous Rice snack bars on the frequency of defecation can be more visible.